NiO/ZnO Core-Shell Nanoparticles In Situ Synthesis Via Microemulsion Method. Issue 5 (3rd May 2016) - Han, D. Y.; Wang, C. Q.; Li, D. D.; Cao, Z. B.
Abstract : Nanoparticles of NiO(core) /ZnO(shell) core-shell and nanoparticles were successfully prepared in Triton X-100/n-hexanol/cyclohexane/water W/O microemulsion system. Basic synthesis conditions were determined. Ni(OH)2 /Zn(OH)2 nanoparticles were first synthesized at room temperature then calcined at 500°C to form NiO/ZnO nanoparticles. The calcined products were studied by means of TEM, and XRD analyzers. The mechanism of the core shell NiO/ZnO nanoparticles formation is explained.